2022
DOI: 10.3390/ijms232315136
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Marine Animal Safety and Marine Bioresources in Response to the SARS-CoV-2 Crisis

Abstract: SARS-CoV-2 as a zoonotic virus has significantly affected daily life and social behavior since its outbreak in late 2019. The concerns over its transmission through different media directly or indirectly have evoked great attention about the survival of SARS-CoV-2 virions in the environment and its potential infection of other animals. To evaluate the risk of infection by SARS-CoV-2 and to counteract the COVID-19 disease, extensive studies have been performed to understand SARS-CoV-2 biogenesis and its pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…On the other hand, monitoring SARS-CoV-2 in bivalve mollusks provides us with an opportunity to explore the potential use of these shellfish as sentinel organisms [ 35 ] since the ability of bivalve mollusks to bioaccumulate the SARS-CoV-2 genome has already been demonstrated. Le Guernic et al performed experiments exposing zebra mussels ( Dreissena polymorpha ) to treated and untreated wastewater from French WWTPs and revealed the presence of the SARS-CoV-2 genome in their digestive tissues in both conditions, analyzing E, RdRp, and N genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, monitoring SARS-CoV-2 in bivalve mollusks provides us with an opportunity to explore the potential use of these shellfish as sentinel organisms [ 35 ] since the ability of bivalve mollusks to bioaccumulate the SARS-CoV-2 genome has already been demonstrated. Le Guernic et al performed experiments exposing zebra mussels ( Dreissena polymorpha ) to treated and untreated wastewater from French WWTPs and revealed the presence of the SARS-CoV-2 genome in their digestive tissues in both conditions, analyzing E, RdRp, and N genes.…”
Section: Discussionmentioning
confidence: 99%
“…Different environmental monitoring investigations have been piloted on the wastewaters of Campania in recent years [ 35 , 38 , 39 , 40 , 41 , 42 , 43 ]. In our study, we collected samples from harvesting areas of Campania and observed that a high percentage of positive mollusk samples corresponded to periods of increased circulation of SARS-CoV-2 in the population [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of effective external defense mechanisms, marine sponges have developed chemical defense strategies through the production of secondary metabolites [6][7][8]] that exhibit, for example, anti-viral [9], anti-inflammatory [10,11] and anti-tumorigenic [12,13] effects. Therefore, a number of these metabolites have been investigated for their potential ability to inhibit infection and replication of SARS-CoV-2 [14,15]. For example, natural inorganic polyphosphate (polyP) has been demonstrated to bind the SARS-CoV-2 spike protein and inhibit interaction with the main receptor angiotensin-converting enzyme 2 (ACE2), along with inducing the degradation of ACE2 on host cells [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%